Occurrence of white finger in the gas industry - Walker, D. Douglas; Jones, Bryan; Ogston, Simon (Scandinavian Journal of Work, Environment & Health, 1986)
A survey was undertaken to study the prevalence of symptoms of white finger in a group of workers who use vibrating tools in the gas industry to break and reinstate road surfaces; the study also compared the level with that found in a reference population having no exposure to vibration. The difference in the prevalence of white finger between the two groups did not reach stat istical significance. The prevalence increased with age, and this relat ionship was statistically significant in each group , but the differences in the prevalences between the survey and reference populations did not reach statistical significance in any of the age groups. White finger sympto ms increased in association with increasing years of usage of vibrating tools, but this phenomenon was shown to be related to age rather than to exposure to vibrat ion . The authors conclude that it would appear that vibration-induced white finger is not currently a particular problem among men who use vibrating tools to break or reinstate road surfaces. That this is the case, however, is possibly more a reflection of the way such tools are used in the gas industry than of the inherent safety of the tools themselves.
Keywords: age effect; gas industry; prevention; questionnaire survey; symptom; vibration exposure; vibration-induced white finger; VWF; VWF unlikely; white finger